Evaluation of Postpartum Sleep Quality and the Influential Factors in the Women in Zanjan City, Iran (2014) - Zahra Behboodi Moghadam; Mahnaz Keshavarz Afshar; Akbar Pourrahimi; Ziba Taghizadeh; Pouran Mokhtari Zanjani; Ali Montazeri (Mashhad University of Medical Sciences, 2018)
Introduction: The postpartum period refers to the first six weeks after delivery, which is associated with significant stress and sleep disorders in women. The present study aimed to evaluate postpartum sleep quality and the influential factors in women. Methods: This cross-sectional study was conducted on 200 women in the postpartum period referring to the health centers in Zanjan, Iran in 2014. Data collection tools were demographic questionnaires, Pittsburgh Sleep Quality Index (PSQI), and Edinburgh Postnatal Depression Scale (EPDS). Data analysis was performed in SPSS version 16 using the Chi-square test, Pearson's correlation-coefficient, and Spearman's correlation-coefficient. P-value of less than 0.05 was considered significant. Results: Mean score of postpartum sleep quality was 7.74±2.31, and 62.5% of the women had low sleep quality during this period. Frequency of waking due to infant's crying (r=0.41; P<0.001) and feeding of the infant (r=0.46; P<0.001) had the most significant correlations with poor sleep quality. In addition, a significant association was observed between maternal depression and poor quality sleep (r=0.16; P=0.03). Among the demographic characteristics, maternal education level (r=-0.37; P=0.004), occupation status of the spouse (P=0.03), age (r=0.28; P=0.02), and maternal occupation status (P=0.03) had significant correlations with sleep disturbance. Conclusion: Considering the poor sleep quality in the women, it is recommended that proper interventions be provided for the prevention and diagnosis of postpartum sleep disorders in addition to the routine care procedures.